O jornalismo de Nelson Rodrigues : a crônica como espaço de intervenção no mundo social - Vannucci, Karine Claussen (2004)
This research intends to demonstrate the singular place that the chroniclers can occupy in the media when defending points of view sometimes not coincident with the ones of the vehicle and the status quo, acting as intellectuals connected to the conflicts of the society where they live and as authorized interpreters of the questions of its time. Based on this understanding, it analyzes the journalism of Nelson Rodrigues, in the conjunction of content and form that distinguished him during the years 1960 and 1970, through the "memories" and "confessions" that he published in the periodicals O Globo and Correio da Manhã . In this way, our objective is to prove that Nelson was a legitimate journalist-intellectual, designating the particular nature of his work, marked by the use of the chronicle as privileged space of intervention in the social world and of the distinctive exercise of the cultural and journalistic authority, and pointing out the prominent place that he occupied in the press and the intellectual field of his time.